Pelaksanaan Tugas dan Wewenang Kepala Desa Dalam Memelihara Ketentraman dan Ketertiban Menurut Undang-Undang Nomor 3 Tahun 2024 Tentang Desa di Desa Kamanasa dan Desa Harekakae Kecamatan Malaka Tengah Kabupaten Malaka - Alberto Paul Barros; David Yohanes Meyners; Mario A. Lawung (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This type of research is empirical juridical, namely the researcher obtains research data directly from related parties or agencies. The population in this study consisted of 2 Village Heads, 4 Hamlet Heads, 6 RT Heads, 4 RW Heads and 10 community members. After the data was obtained, the researcher will group the data based on the data source and analyze it to get answers to the problem formulation in this study. The results of the study indicate that (1) the implementation of the duties and authorities of the Village Head has not been running well. This is evidenced by the community who still do not feel peace and order in the environment. The Village Head must conduct more routine socialization on how to maintain peace and order to the community. (2) The inhibiting factors for the Village Head in carrying out the duties and authorities of maintaining peace and order, namely there are still many riots, fights between martial arts schools and the lack of facilities and infrastructure provided, to support the creation of peace and order in the community. The author's suggestion in this study is that the Village Head must conduct more frequent socialization and increase motivation to the community to maintain peace and order in their environment. This can be done through religious activities involving young people, thus encouraging them to do more positive activities rather than activities that disturb the peace of other communities.